Detection and discrimination of chromatic targets in hemianopic macaque monkeys and humans. - Cowey, A; Stoerig, P (2001)
We measured the ability of three macaque monkeys with unilateral removal of primary visual cortex to detect 9 degrees, 200-ms targets presented at random in the upper or lower quadrants of the normal and hemianopic visual fields. The white or variously coloured target could differ from the background in both colour and luminance, or in either of them. Blue and red targets were detectable at any luminance contrast, but green and white targets were barely or not at all detectable at and near isoluminance in the hemianopic field. Blue and red targets were better detected than white targets at the same luminance difference. However, when both the target and the background were dynamically luminance-masked, detection in the hemianopic field failed at isoluminance whatever the colour. In addition, the monkeys were unable to discriminate between simultaneously presented red and green or blue and green targets in the hemianopic field when both targets had similar luminance contrast with the background. Two hemianopic patients tested on a subset of the tasks performed similarly to the monkeys. Together, the results indicate that the residual colour-opponent system that survives damage to V1 is involved in the detection of chromatic changes but cannot sustain simultaneous discrimination between pairs of colours.